1996
DOI: 10.1021/ef950257w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Drying Methods on Coal Structure and Reactivity Toward Liquefaction

Abstract: Different methods of drying coal were investigated to determine if drying can be accomplished without altering the coal structure and reactivity toward liquefaction. Coal-drying methods included thermal and microwave drying at elevated temperatures and chemical drying at low temperature. Six coals from lignite to high volatile bituminous rank were studied. Laboratoryscale liquefaction experiments were carried out on premoisturized and dried coals to determine the effects of different drying methods on liquefac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…These effects, however, diminish with increasing rank and it has been suggested that drying does not significantly alter the structure of bituminous coals (Miknis et al, 1996). To avoid the effects of structural changes induced by drying, which may affect the sorption results, the samples selected for this study were all bituminous coals.…”
Section: Samplesmentioning
confidence: 99%
“…These effects, however, diminish with increasing rank and it has been suggested that drying does not significantly alter the structure of bituminous coals (Miknis et al, 1996). To avoid the effects of structural changes induced by drying, which may affect the sorption results, the samples selected for this study were all bituminous coals.…”
Section: Samplesmentioning
confidence: 99%
“…By swelling pretreatment, coal molecules can be dissociated, rearranged and re-associated in lower free energy conformations, or probably in a different molecular structure. The swelling solvents may break weaker bonds, create macro-pores or enhance the coal porosity, and hence facilitate the dispersion of the catalyst onto the coal structure, and more importantly assist the dispersion of the hydrogen donor solvent into the coal [37][38][39]. The yields of liquefaction products were strongly dependent on the type of swelling solvent used.…”
Section: Swelling Treatmentmentioning
confidence: 99%
“…Although it is commonly believed that the swelling solvents can enhance the coal porosity, and improve the dispersion of the catalyst onto the coal structure as discussed above [37][38][39], negative impacts of the swelling solvents were also observed [41,43,44]. Shui et al [44] demonstrated that the presence of swelling solvents in the swollen coal was detrimental for the subsequent liquefaction of the swollen coal.…”
Section: Swelling Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary information about this type of coal was shown in Table 1 and Table 2, tested by Saghafi and Roberts (2008) from CSIRO. It is widely recognised that thermal drying of low rank coals can cause irreversible coal structure changes and these effects can be diminish with increasing rank and it has been reported that drying does not significantly change the structure of bituminous coals (Miknis et al, 1996). The bituminous coal from Bulli Seam of the Sydney Basin is suitable to carry the test to avoid the effects of structural change induced by drying, which may affect the isotherm results of this study.…”
Section: Sample Preparationmentioning
confidence: 98%